On the relation between measures defining the Stieltjes and the inverted Stieltjes functions - Gilewicz, J.; Pindor, M. (Український математичний журнал, 2010)
A compact formula is found for the measure of the inverted Stieltjes function expressed by the measure of the original Stieltjes function. Встановлено формулу для міри оберненої функції Стільтьєса, що виражена через міру початкової функції Стільтьєса.